Biochemical and histological alterations induced by nickel oxide nanoparticles in the ground beetle Blaps polychresta (Forskl, 1775) (Coleoptera: Tenebrionidae). - Saeed El-Ashram (Public Library of Science (PLoS), 2021)
The present study evaluates the effect of nickel oxide nanoparticles on some biochemical parameters and midgut tissues in the ground beetle Blaps polychresta as an indicator organism for nanotoxicity. Serial doses of the NiO-NPs colloid (0.01, 0.02, 0.03, 0.04, 0.05, and 0.06 mg/g) were prepared for injecting into the adult beetles. Insect survival was reported daily for 30 days, and the sublethal dose of 0.02 mg/g NiO-NPs was selected for the tested parameters. After the treatment, nickel was detected in the midgut tissues by X-ray microanalysis. The treated group demonstrated a significant increase in aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities when compared to the untreated group. However, the treated group demonstrated a significant decrease in ascorbate peroxidase (APOX) activity when compared to the untreated group. Histological and ultrastructural changes in the midgut tissues of treated and untreated beetles were also observed. The current findings provide a precedent for describing the physiological and histological changes caused by NiO-NPs in the ground beetle B. polychresta.